PERENCANAAN URBAN GREEN SPACE DALAM MERESPON COVID-19: Studi Kasus Kebun Buah Eduwisata Bendosari - Hindun Nadlifah (UIN Sunan Kalijaga, 2021)
Bendosari Eduwisata Fruit Garden is a natural laboratory assisted by the Center for Development and Community Service, a work unit under the auspices of the Research and Community Service Institute (LPPM) of UIN Sunan Kalijaga Yogyakarta. This research is a guide in the further development of the master plan for the Bendosari Eduwisata Fruit Garden in the design development phase, before entering the final phase, namely the final master plan in the form of construction documents. The methodology used is descriptive qualitative research method. The initial stage is carried out by conducting interviews and focus group discussions with garden managers and the surrounding community. Then proceed with conducting a site analysis and study of precedents. Based on the collected data, a schematic master plan is then designed which is composed of site analysis and programming, adjusting to the needs and surrounding conditions. The Bendosari area is prepared to become an urban green space area that is resilient or able to withstand any situation such as the current Covid-19 pandemic. This design focuses on community empowerment through a participatory approach and learning together which aims to prosper the community around the orchard area, both in terms of economy and environmental health.